IMPLEMENTASI DIGESTER BIOGAS PORTABLE DARI DRUM 200 L SEBAGAI GAS RUMAH TANGGA BERBASIS LIMBAH TERNAK SAPI DI ALUE IE PUTEH ACEH TAMIANG - Teuku Andi Fadlly; Rahmawati Rahmawati; Rachmad Almi Putra; Alamsyah Wan (LPPM dan PM Universitas Samudra, 2020)
Implementation of portable biogas digester as domestic gas-based cattle waste has been done. Biogas contributes to reducing negative externalities associated with organic waste such as groundwater and soil pollution and emissions of local air pollutants. In addition, biogas is a renewable energy source. Alue Ie Puteh is a village located in Manyak Payed District, Aceh Tamiang Regency has an area of ± 650 hectares. Produced through anaerobic digestion of biodegradable organic raw materials, one of which is animal residues that produce high methane gas content (40-70%). The area of plantations and rice fields of the village is very wide, so that the average community farms and raises cattle. Cage waste in the form of cow dung in the village has not been maximally utilized and just piled up. The lecture method was carried out by providing information to the public about the benefits of portable biogas digester as an alternative gas product and organic fertilizer. Practice method is done by providing information to the public how to manufacture portable biogas digester, cheap and safe. The results obtained that the community was very enthusiastic in participating in the implementation of a portable biogas digester made from cattle cage waste so that the activity went smoothly, thus increasing the insights and skills of the community. In addition to this, increasing the economy of the community in a fuel crisis by utilizing alternative gas to reduce the need for LPG for households. Biogas digester side products such as organic fertilizer that can be used for agriculture. The methane gas generated in the portable biogas digester with a capacity of 200 L in 20 days can boil water.